If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 = u + -6 Reorder the terms: -9 = -6 + u Solving -9 = -6 + u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-1u' to each side of the equation. -9 + -1u = -6 + u + -1u Combine like terms: u + -1u = 0 -9 + -1u = -6 + 0 -9 + -1u = -6 Add '9' to each side of the equation. -9 + 9 + -1u = -6 + 9 Combine like terms: -9 + 9 = 0 0 + -1u = -6 + 9 -1u = -6 + 9 Combine like terms: -6 + 9 = 3 -1u = 3 Divide each side by '-1'. u = -3 Simplifying u = -3
| 4a+6a+8b-5b= | | 3x+7=15-12x | | -3w-(-9)=12 | | P(t)=5t^2+12t+2 | | z/3.5=4 | | 47-11=36 | | 2(12.5-4x)+2x=11.5 | | 9-16y^2=0 | | 42/0.2 | | 5(7a-8)=-320 | | 12z=168 | | 2(12.5-4x)+2y=11.5 | | 4y+2.6y=36 | | 2x+7=x+7+x | | 3x-2sin(x)+7=0 | | (a-bi)(3+5i)=0 | | 9x^3-6x^2-6x+4=0 | | 2(w+3)-8w-1= | | 5x+14=4+3x | | 7(b-4)=-84 | | 3z+20=(-55) | | x-x*.17=24070 | | 7x-4+2x=5 | | n-16=21 | | 8(2n+6)=112 | | 8.304/16 | | 4x+10-6+4=20 | | 2/5x=6/35 | | 2xsquare=8x | | 4(6-5x)=164 | | -8w+10=5 | | 2(3x-18)=0 |